Persepsi Mahasiswa Akuntansi terhadap Profesi Audit di Kota Semarang: Pengaruh Kedekatan dan Pengetahuan terhadap Stereotip Auditor - Fadhilatul Munawaroh; Sri Anik (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The shortage of professional auditors in Indonesia is partly influenced by accounting students’ perceptions and stereotypes about the auditing profession. Negative stereotypes often discourage students from pursuing auditing careers, while positive perceptions may enhance their professional interest. This study aims to examine the influence of familiarity and knowledge on accounting students’ stereotypes of the auditor profession in Semarang City. The research employed a quantitative explanatory approach using a purposive sampling technique with 393 respondents who had taken auditing courses. Data were collected through structured questionnaires and analyzed using multiple linear regression and t-tests with SPSS 26. The findings reveal that both familiarity and knowledge significantly and positively affect students’ stereotypes of the auditor profession. Students with higher exposure and understanding of auditing tend to perceive the profession more positively, associating it with responsibility and professionalism rather than rigidity. These results highlight the importance of academic programs and practical exposure in shaping students’ perceptions and reducing negative stereotypes toward auditors.